Plasma-Assisted Nanofabrication: The Potential and Challenges in Atomic Layer Deposition and Etching - Chiappim, William [UNESP]; Neto, Benedito Botan; Shiotani, Michaela; Karnopp, Júlia; Gonçalves, Luan; Chaves, João Pedro; Sobrinho, Argemiro da Silva; Leitão, Joaquim Pratas; Fraga, Mariana; Pessoa, Rodrigo (MDPI, 2022)
The growing need for increasingly miniaturized devices has placed high importance and demands on nanofabrication technologies with high-quality, low temperatures, and low-cost techniques. In the past few years, the development and recent advances in atomic layer deposition (ALD) processes boosted interest in their use in advanced electronic and nano/microelectromechanical systems (NEMS/MEMS) device manufacturing. In this context, non-thermal plasma (NTP) technology has been highlighted because it allowed the ALD technique to expand its process window and the fabrication of several nanomaterials at reduced temperatures, allowing thermosensitive substrates to be covered with good formability and uniformity. In this review article, we comprehensively describe how the NTP changed the ALD universe and expanded it in device fabrication for different applications. We also present an overview of the efforts and developed strategies to gather the NTP and ALD technologies with the consecutive formation of plasma-assisted ALD (PA-ALD) technique, which has been successfully applied in nanofabrication and surface modification. The advantages and limitations currently faced by this technique are presented and discussed. We conclude this review by showing the atomic layer etching (ALE) technique, another development of NTP and ALD junction that has gained more and more attention by allowing significant advancements in plasma-assisted nanofabrication.
Keywords: ALD; non-thermal plasma; plasma-assisted atomic layer deposition; plasma-atomic layer etching; plasma-enhanced atomic layer deposition; radical-enhanced atomic layer deposition; thin-film